Preventing Ventilator-Associated Lung Injury: A Perioperative Perspective - Kimura, Satoshi; Stoicea, Nicoleta; Rosero Britton, Byron Rafael; Shabsigh, Muhammad; Branstiter, Aly; Stahl, David L. (Frontiers in Medicine, 2016)
Introduction: Research into the prevention of ventilator-associated lung injury (VALI) in patients with acute respiratory distress syndrome (ARDS) in the intensive care unit (ICU) has resulted in the development of a number of “lung protective strategies,” which have become commonplace in the treatment of critically ill patients. An increasing number of studies have applied lung protective ventilation in the operating room to otherwise healthy individuals. We review the history of lung protective strategies in patients with acute respiratory failure and explore their use patients undergoing mechanical ventilation during general anesthesia to provide context for a discussion of the benefits and drawbacks, as well as inform future areas of inquiry. Methods: We completed a database search and reviewed articles investigating lung protective ventilation in both the ICU and in patients receiving general anesthesia through May 2015. Results: Lung protective ventilation was associated with improved outcomes in patients with acute respiratory failure in the ICU. Clinical evidence is less clear regarding lung protective ventilation for patients undergoing surgery. Conclusion: Lung protective ventilation strategies including low tidal volume ventilation and moderate positive end-expiratory pressure (PEEP) are well established therapies to minimize lung injury in critically ill patients with and without lung disease, and may provide benefit to patients undergoing general anesthesia.